Bioassay activity of crude bacteriocin produced by Lactobacillus acidophilus isolate against cold stressed E.coli O157:H7: Najim Hadi Najim , Zuhair Ahmad Mohammed and Zina Saab khudhir - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2012)
The laboratory studies of the cultural isolation revealed that two isolates of Lactobacillus acidophilus were isolated from five soft cheese samples that were manufactured locally according to the farmers production procedure .Colonies of E.coli O157:H7 were isolated from raw milk samples by a conventional direct plating on selective enrichment CT-SMAC agar and tested serologically for the presence of O157 and H7 antigens using the commercial available latex agglutination kits .The results revealed that E.coli O157:H7 was resist to the crude bacteriocin that was extracted from L .acidophilus isolate NO.1 due to the nature of their cell wall, while when the outer membrane of E.coli O157:H7 was injured by cooling at 4°C for 6 hours , the permeation of bacteriocin to the cytoplasmic membrane was facilitated and caused inactivation and death of such pathogenic organism .The results revealed that no growth of E.coli O157:H7 with no visible turbidity in the nutrient broth with bacteriocin that diluted to 1\2 ,1\4 ,1\8 were observed .Bacteriocin that diluted to 1\8 had been recognized as the minimum inhibitory concentration of the bacteriocin.Both the dilution factor of bacteriocin and time exposure to bacteriocin at refrigeration storage temperature of milk had a significant (P˂0.05) influence on its antimicrobial potency against the viability of stressed E.coli O157:H7 from minutes 30 to 120 .The viability of E.coli O157:H7 subjected to bacteriocin that diluted 10 times(1:10) in both raw and sterile milk was efficiently eliminated after 90 minutes and 60 minutes of exposure at refrigeration temperature respectively.